The Classification of Chest Radiographs for Coalworkers' Pneumoconiosis: A Study of the Performance of Two Readers Over a Period of Six Years - Ashford, J. R. (1960)
The paper is concerned with the performance over the past six years of the two doctors responsible for the classification of chest radiographs obtained by the National Coal Board's Pneumoconiosis Field Research. A brief description is given of the categories of pneumoconiosis used in the Research and of the procedures adopted to decide the final or “definitive” classification. The readings obtained are then considered in detail and three main points emerge from the analysis. First, it is shown that there have been marked systematic fluctuations in the reading levels of these two very experienced observers. In spite of these individual variations it is found that the standards applied on the definitive readings, which are based on the joint discussion by the two doctors of films on which their individual readings are inconsistent, remain remarkably constant over a period of several years. The third main feature of the analysis is the considerable differences in the magnitude of the reading errors between the various categories of pneumoconiosis. It is concluded that, although the existing procedures provide a satisfactory way of estimating the prevalence of pneumoconiosis, it would be desirable to increase the number of film readers. The beneficial effect of the system whereby a running check is kept on film reading standards is also established.